Rationale and design of the Dapagliflozin after Transcatheter Aortic Valve Implantation (DapaTAVI) randomized trial. (9th November 2021) - Amat‐Santos, Ignacio J.; Sánchez‐Luna, Juan P.; Abu‐Assi, Emad; Melendo‐Viu, María; Cruz‐Gonzalez, Ignacio; Nombela‐Franco, Luis; Muñoz‐Garcí, Antonio J.; Blas, Sergio G.; de la Torre Hernandez, Jose M.; Romaguera, Rafael; Sánchez‐Recalde, Ángel; Diez‐Gil, José L.; et al.
Abstract: Aims: Despite aortic stenosis (AS) relief, patients undergoing transcatheter aortic valve implantation (TAVI) are at increased risk of developing heart failure (HF) within first months of intervention. Sodium–glucose co‐transporter 2 (SGLT‐2) inhibitors have been shown to reduce the risk of HF hospitalization in individuals with diabetes mellitus, reduced left ventricular ejection fraction and chronic kidney disease. However, the effect of SGLT‐2 inhibitors on outcomes after TAVI is unknown. The Dapagliflozin after Transcatheter Aortic Valve Implantation (DapaTAVI) trial is designed to assess the clinical benefit and safety of the SGLT‐2 inhibitor dapagliflozin in patients undergoing TAVI. Methods: DapaTAVI is an independent pragmatic, controlled, prospective, randomized, open‐label blinded endpoint, multicentre trial conducted in Spain, evaluating the effect of dapagliflozin 10 mg/day on the risk of death and worsening HF in patients with severe AS undergoing TAVI. Candidate patients should have prior history of HF admission plus ≥1 of the following criteria: (i) diabetes mellitus, (ii) left ventricular ejection fraction ≤40%, or (iii) estimated glomerular filtration rate between 25 and 75 ml/min/1.73 m 2 . A total of 1020 patients will be randomized (1:1) to dapagliflozin vs. no dapagliflozin. Key secondary outcomes include: (i) incidence rate of individual components of the primary outcome; (ii) cardiovascular mortality; (iii) the composite of HF hospitalization or cardiovascular death; and (iv) total number of HF rehospitalizations. Conclusion: DapaTAVI will determine the efficacy and safety of dapagliflozin in a broad spectrum of frail patients after AS relief by TAVI.